Catalytic synthesis, spectral characterization, antimicrobial and molecular docking studies on some novel [E]-N-phenyl-3, 5-dichloropyridin-4-amine and its derivatives. (2022) - Selvakumar, G.; Palanivel, C.
Abstract: The present methodology offers a domino reaction strategy, high yield, simpler operation, recyclable and environmentally friendly. A number of [E]-N benzylidene-3, 5-dichloropyridine-4-amines were synthesized from 3, 5-dichloropyridine-4-amine and aromatic aldehydes with 5 mol% of nanocatalyst. IR and NMR spectroscopic techniques characterized structures of all synthesized compounds. The antimicrobial activities were screened for all synthesized [E]–N‐benzylidene-3, 5-dichloropyridine-4-amines. Docking studies with DNA Gyrase receptor have been conducted. Comparison of Docking scores with standard ciprofloxacin medicinal products. Most of the synthesized compounds have been well suited to all the docked targets at the working site.